In Vitro Antioxidant Activity and In Vivo Hepatoprotective Effects of Ethanolic Extracts from Wall-Broken Ganoderma Lucidum Spores - Thuy, Nguyen Huu Lac; Diem, Vo Thi; Thuong, Trinh Thi Dieu; Anh, Tran Tuyet; Nhut, Truong Minh; Dat, Truong Van; Trinh, Huynh Ngoc (Open Access Macedonian Journal of Medical Sciences, 2022)
The wall-broken Ganoderma lucidum spores are widely used in recent years in the belief that active components inside the spores are better released and well absorbed when taken orally. In this study, the sporoderm of G. lucidum was broken by autoclaving at a high temperature. The powder of wall-broken spores was then extracted by soaking with ethanol at different concentrations (50 %, 70 % and 96 %). The 70% and 50% ethanol extracts had the highest total triterpenoid content, in which ganoderic acid A was predominant. In the DPPH free radical scavenging test, 70% ethanol extract exhibited the highest in vitro antioxidant activity. This 70% ethanol extract was also safe in mice at the dose of 2,000 mg/kg body weight. Moreover, this extract protected the liver from acute injury induced by cyclophosphamide. Indeed, the pretreatment by oral administration of 70% ethanol extract prevented serum ALT and AST activities elevation and attenuated hepatic MDA formation and GSH depletion following administration of cyclophosphamide in mice.